CASE STUDY: PARAPHIMOSIS IN A CASTRATED MIX DOG - Putra, Anak Agung Wisnu Kusuma; Gunawan, Stefanus Andre; Pemayun, I Gusti Agung Gde Putra (Buletin Veteriner Udayana, 2022)
This purpose of this article is to determine the successful treatment of paraphimosis case in a dog. Handling of paraphimosis in this case is using the surgical method by making an incision in the ventral prepuce and repositioning the penis into the prepuce cavity. The case dog is a male kintamani mix dog castrated age of 14 years old with a body weight of 15,3 kg with the colour black. The dog penis was reported not being able to retract back to its normal state for 2 days and the dog have no appetite with no sign of urination and defecation. Physical examination shown the dog have no appetite with no sign of urination and defecation, the dog was seen having dysfunction of the hind legs when walking since childhood according to the owrner. By anamnesis and physical examination the dog was diagnosed with paraphimosis. Post operation treatmen given to the dog were Cephalosporin antibiotics, namely cefotaxime (dosage 20mg/kg body weight, IV, q12h) for 3 days and cefixime (dosage 10mg/kg body weight, PO, q12h) continuing from day 4 to day 6, anti-inflammatory dexamethasone (dosage 0,01 mg/kg body weight, IM, q24h) for 5 days post operation. 7 days post operation result were the dog recovered with no problems.